(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Wireless Sensor Systems (WSNs) is a standard wellspring of information gathering and detecting instrument for a broad assortment of uses, for instance, condition observing, agriculture, prosperity, military, and keen transportation. Each sensor hub accumulates data from the earth and advances this recognized information to Base Station (BS) through a wireless connection in either single-bounce or multi-jump way. This information gathering and sending property of the sensor hubs to run the central essentialness usage factor of a system. These sensor hubs are furnished with low power batteries which may be difficult to replace, making it a significant research zone to structure imperativeness gainful conventions. To beat this issue the WSN puts new difficulties especially in planning of directing conventions. The protocols are divided into clustering and non-clustering based protocols. The clustering based routing protocols proven effective over the conventional non-clustering protocols. However, there are very few works attempted for exploiting the mobile agents in WSN clustering to optimize the energy efficiency performance further. The review and analysis of such mobile agent based clustering protocols presented in this paper. We presented the study of design of mobile agent based clustering methods for WSNs in this paper. At last, we abridge and finish up the paper with some future headings.